Development of the Computer and Technology Attitude Questionnaire (CaTAQ) to inform performance on computerised cognitive testing in older adults in the CogSCAN Study: Neuropsychology/computerized neuropsychological assessment. (7th December 2020) - Croot, Karen; Allison, Karen C.; Sachdev, Perminder S.; Brodaty, Henry; Crawford, John D.; Lam, Ben C.P.; Lee, Teresa; Henry, Julie D.; Draper, Brian; Close, Jacqueline; Ong, Min Yee; Rossie, Matilda; et al.
Abstract: Background: Computer‐administered neuropsychological assessment batteries (CNAs) have the potential to allow large‐scale cognitive screening and monitoring, increasing older adults' access to cognitive assessment, and earlier diagnosis of and intervention for cognitive impairment. There is, however, little research on whether experience with and attitudes to computers and technology affect the validity, reliability and acceptability of CNAs in older adults. Here, we report the development and validation of an instrument to measure computer attitudes and computer experience in an older adult cohort from the CogSCAN study. Method: The Computer and Technology Attitude Questionnaire (CaTAQ) is a new 27‐item self‐report questionnaire comprising five subscales (computer anxiety, comfort with computers, positive and negative attitudes to computers and computer learning self‐efficacy) that have been individually validated in diverse populations (young, predominantly Hispanic Los Angeles adults; Canadian business employees; older Pennsylvanian Caucasian adults), as well as items measuring experience with computers and related technologies. Responses from 196 community‐living older adults without dementia in Sydney, Australia (67% female, mean age 72.1 years, range 60‐91 years, mean years' education 14.7, limited/no computer experience 9.2%) have been analysed to date. Result: Confirmatory factor analysis supported a three‐factor model (anxiety/discomfort, positive about technology, negative about technology) with good fit to items from the first four subscales (Figure 1), and four computer learning efficacy items formed a single factor with good fit in a subsample of 79 participants who reported not knowing how to use a computer (Figure 2). Our measurement models for this older Australian sample therefore replicate previous validation of these subscales. Analyses in progress will further clarify the factor structure of the questionnaire and remove redundant items. Conclusion: Results suggest the CaTAQ can provide nuanced information about older adults' attitudes to computers and technology that have the potential to influence CNA performance and acceptability. The results will need to be confirmed in a less‐educated sample with less computer experience, and in people with Mild Cognitive Impairment or mild dementia. This new instrument has the potential to inform decisions about suitability of computerised cognitive testing for older adults in research and clinical settings.